Validitas Game Edukasi Klasifikasi Tumbuhan Berbasis Permainan Koa sebagai Media Pembelajaran Biologi - Rahmadhani Fitri; Relsas Yogica (Department of Biology Education, Faculty of Education and teacher Training, Maritime University of Raja Ali Haji, 2018)
ABSTRACT. Based on observations, not many teachers or lecturers who use educational games are mainly to facilitate students in learning material about taxonomy, especially the classification of plants. Educational game classification of plants based on the koa game is expected to function to facilitate students in learning the classifications that are classified as difficult to memorize. This research is research development. Data collection was carried out by expert validation of educational games and data were analyzed using descriptive statistical analysis. Based on the results of the game education analysis obtained the value of the validity of the game education classification of plants is 89.13 with valid criteria. It can be concluded that the educational game based on koa game is valid, and practicality tests can be done to see the level of practicality of the game. ABSTRAK. Berdasarkan hasil observasi yang dilakukan, belum banyak guru ataupun dosen yang menggunakan game edukasi terutama untuk memudahkan peserta didik dalam mempelajari materi mengenai taksonomi khususnya klasifikasi tumbuhan. Game edukasi klasifikasi tumbuhan berbasis permainan koa diharapkan dapat berfungsi untuk memudahkan peserta didik dalam mempelajari klasifikasi yang tergolong susah untuk dihafalkan. Penelitian ini merupakan penelitian pengembangan. Pengumpulan data dilakukan dengan memvalidasi game edukasi oleh pakar dan data dianalisis menggunakan analisis statistik deskriptif. Berdasarkan hasil analisis game edukasi didapatkan nilai validitas game edukasi klasifikasi tumbuhan adalah 89,13 dengan kriteria valid. Dapat disimpulkan bahwa telah dihasilkan game edukasi berbasis permainan koa yang valid dan selanjutnya dapat dilakukan uji praktikalitas untuk melihat tingkat kepraktisan game tersebut.